1995
DOI: 10.1111/j.1748-7692.1995.tb00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Bottom Feeding by Humpback Whales on Stellwagen Bank

Abstract: Humpback whales, Megaptera novaeangliae, on Stellwagen Bank off eastern Massachusetts, U.S.A., apparently bottom feed on northern sand lance, Ammodytes dubius. The feeding behavior is characterized by the whales brushing the bottom in depths of less than 40 m, causing sand lance burrowed in the bottom to be flushed up into the water column. The greatest densities of sand lance were in beds of shells and shell debris, termed "shell hash." The brushing against or along the bottom, particularly in these shell has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 16 publications
(16 reference statements)
3
54
0
Order By: Relevance
“…A bottom feeding event was defined using the hypothesis presented by Hain et al (1995) that humpback whales bottom feed on Stellwagen Bank by rolling on their side and 'brushing' the bottom, typically using the right side of their mouth. Ware et al (2006) use this information to code the ribbon plots in Trackplot to highlight any off axis roll of > 40°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A bottom feeding event was defined using the hypothesis presented by Hain et al (1995) that humpback whales bottom feed on Stellwagen Bank by rolling on their side and 'brushing' the bottom, typically using the right side of their mouth. Ware et al (2006) use this information to code the ribbon plots in Trackplot to highlight any off axis roll of > 40°.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral studies and laboratory research have shown that sand lance burrow into sandy substrate at night and during times of relatively low density, and migrate vertically during daylight hours forming dense schools (Winslade 1974, Meyer et al 1979. Concurrent to the increase in sand lance dominance in the area, Hain et al (1995) described apparent bottom feeding on sand lance by humpback whales on Stellwagen Bank based on the presence of rostral abrasions and scars and an absence of observed surface feeding observations during the same periods.…”
Section: Introductionmentioning
confidence: 90%
“…Depleted stocks are more vulnerable to changes in the environment (Brander 2005) and are therefore much more likely to crash. A decline in the North Sea sandeel stock will affect up to 10 species of predatory fishes (Engelhard et al 2008), as well as a number of bird species and marine mammals (Furness 1990, Hain et al 1995, Furness 2002, Frederiksen et al 2005.…”
Section: Perspectivesmentioning
confidence: 99%
“…In many ecosystems sandeel is a key prey fish linking trophic levels (Furness 1990, 2002, Hain et al 1995, Frederiksen et al 2005. The lesser sandeel Ammodytes marinus constitutes the vast majority of sandeels in the North Sea and one of the largest fish biomasses (Temming et al 2004, ICES 2005, and has supported a large industrial fishery since the 1950s.…”
Section: Introductionmentioning
confidence: 99%
“…For animals feeding in the SW Gulf of Maine, particularly on Stellwagen Bank, sand lance (Ammodytes spp.) are thought to be among the primary prey species [48][49][50]. Humpback whale aggregations in the SW Gulf of Maine were shown to be significantly correlated with areas of sand lance abundance [48].…”
Section: Ecological and Biological Factors Affecting Contaminant Loadsmentioning
confidence: 99%